Abnormal myocardial and coronary vasculature development in experimental hypoxia - Nanka, Ondrej; Krizova, Petra; Fikrle, Michal; Tuma, Michal; Blaha, Milan; Grim, Milos; Sedmera, David (Anatomical record (Hoboken, N.J., 2008)
Oxygen availability is one of the necessary prerequisites for normal embryonic development. In our previous study we found that quail embryos incubated under hypoxic conditions (16% O(2)) die at embryonic day (ED) 9 with signs of heart failure. By ED4 and ED6 we found thinner ventricular wall and increased capillary density. We thus hypothesized that the cause of death would lie in severe myocardial and coronary maldevelopment. ED6 and 7 hypoxic hearts had thinner ventricular wall, especially left. There was a simultaneous increase in capillary density, most pronounced in the interventricular septum. This site corresponds to an area of tissue hypoxia and ensuing increased angiogenesis, and also formation of ventricular conduction system. Hypoxia had a positive effect on normal sequence of maturation of the conduction system evaluated by optical mapping at ED7. In sections from ED9 hypoxic hearts we found, in addition to thinner ventricular walls, irregularities in development of coronary tree (missing coronary ostia, absence of one coronary artery, and irregular arterial wall). This deficiency was due to decreased myocyte proliferation rather than to increased apoptosis. By Indian ink injection through the left ventricle we found in normoxic hearts regular coronary branching pattern, while in the hypoxic ones there was often only an irregular plexus. Embryonic hypoxia thus leads to increased capillarity and trabeculation to minimize diffusion distance. In the subsequent period there is a failure in organization of vascular plexus into normal vasculature, resulting in thin compact myocardium that likely leads to heart failure and embryonic death.
Keywords: patologická angiogeneze; Coronary Vessels; Embryo, Nonmammalian; fenotyp; Capillaries; Phenotype; cévní endotel; Cell Proliferation; srdce; Embryonic Development; Heart Conduction System; Hypoxia; Endothelium, Vascular; kardiomyocyty; Animals; převodní systém srdeční; zvířata; Neovascularization, Pathologic; Myocytes, Cardiac; koronární cévy; embryonální vývoj; proliferace buněk; kapiláry; Heart; hypoxie; embryo nesavčí; Coturnix